2013
DOI: 10.1097/sla.0b013e3182504665
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Gastric Pouch Enlargement With Adjustable Gastric Banding in Premenopausal Women

Abstract: Younger women are at higher risk of PPD after LAGB surgery than men and women older than 50 years. Sex hormones may play a role in predisposing to gastric stretch after surgery. These findings may apply more broadly to the gastric "restrictive" component of other bariatric procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…In addition, in this study, the gastroesophageal dilatation was observed only in women that may be related to sex hormones especially progesterone. 34 Our results indicated that the rate of patient's dissatisfaction with the band was 35.4%; however, Himpens et al 21 have reported that 25.6% of patients dissatisfied with the band. Studies published previously have reported that the rate of weight loss failure within 1 year after operation is 10% to 20% and it increases over the time, 28 whereas the patient's dissatisfaction because of weight loss failure developed at least 4 years postoperation in this study.…”
Section: Figurementioning
confidence: 69%
“…In addition, in this study, the gastroesophageal dilatation was observed only in women that may be related to sex hormones especially progesterone. 34 Our results indicated that the rate of patient's dissatisfaction with the band was 35.4%; however, Himpens et al 21 have reported that 25.6% of patients dissatisfied with the band. Studies published previously have reported that the rate of weight loss failure within 1 year after operation is 10% to 20% and it increases over the time, 28 whereas the patient's dissatisfaction because of weight loss failure developed at least 4 years postoperation in this study.…”
Section: Figurementioning
confidence: 69%
“…A second clinically important observation was that women and lower age were independently associated with an increased risk of PPD requiring revision [3]. Exploring the data proved interesting as the age effect was restricted to women with younger women at a higher risk, and men and post menopausal women at much lower risk.…”
mentioning
confidence: 99%